PENINGKATAN KUALITAS PEMBELAJARAN ETNOMATEMATIKA BERBANTUAN MEDIA STIKER-KALENDER DAN BATU WARNA PADA SISWA SEKOLAH DASAR - Shinta Pramudya Kusuma Wardani; Julianto; Ayu Intan Nurul Auliya; Rahmat Arifin; Fitria Hidayati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Teachers methods tend to be focused on a mechanistic and algorithmic curriculum, making mathematics is scary and unattractive for students which is not in accordance with the characters and learning paths of students who are different. This research aims to improve the quality of learning from teachers and students at the fifth grade elementary school level by analyzing the characteristics of a realistic mathematics-based learning flow with a cultural approach of multiple material. The research method used is the classroom action research method which adopts the Kemmis & McTaggart model which consists of several cycle stages starting from the planning stage using calendar media, color stickers, color stones, and LKPD, action stage, observation stage, and reflection stage, while the technique The data analysis used is qualitative and quantitative descriptive techniques. The results obtained from this research are the use of one dominant medium is more effective, the importance of increasing practices, and detailing instructions. The improvement in learning quality can be seen from the results of calculating the percentage of evaluation, in the pre-cycle stage there were 5 students (17.85%) who reached the standard, 17 students (60.72%) in cycle 1, and 26 students in cycle 2 ( 92.85%). The responses shown by the students showed that the students were very interested and happy with this learning, their understanding of the cultural and mathematical context increased, and there were no significant difficulties after going through 3 improvement cycles. Thus, the researcher concluded that this research had met the research objectives.